β-Hemoglobinopathies: The Test Bench for Genome Editing-Based Therapeutic Strategies - Barbarani, Gloria; Łabedz, Agata; Ronchi, Antonella Ellena (Frontiers in Genome Editing, 2020)
Hemoglobin is a tetrameric protein composed by two  and two β chains, each containing a heme group that reversibly binds oxygen. The composition of hemoglobin changes during development in order to fulfill the need of the growing organism, stably maintaining a balanced production of -like and β-like chains in a 1:1 ratio. Adult Hemoglobin (HbA) is composed by two  and two β subunits (2β2 tetramer), whereas Fetal Hemoglobin (HbF) is composed by two  and two  subunits (22tetramer). Qualitative or quantitative defects in β-globin production cause two of the most common monogenic inherited disorders: β-Thalassemia and Sickle Cell Disease. The high frequency of these diseases and the relative accessibility of hematopoietic stem cells make them an ideal candidate for therapeutic interventions based on genome editing. These strategies move in two directions: the correction of the disease-causing mutation and the reactivation of the expression of HbF in adult cells, in the attempt to re-create the effect of HPFH (Hereditary Persistence of Fetal Hemoglobin) natural mutations, which mitigate the severity of β-hemoglobinopathies. Both lines of research rely on the knowledge gained so far on the regulatory mechanisms controlling the differential expression of globin genes during development.